IMPLEMENTASI KEBIJAKAN KOEFISIEN DASAR BANGUNAN OLEH PEMUKIM DI PERUMAHAN BUKIT SEMARANG BARU KECAMATAN MIJEN KOTA SEMARANG - Pratomo, Joko (Geo-Image, 2016)
The aim of in this research are: 1)Understanding the implementation. Building coverage home in the Housing BSB District of Mijen Semarang City, 2) Analyzing the forms of violation building coverage in Housing BSB and why, 3) Creating a map of the landing priority handling of violations building coverage in Housing BSB District of Mijen Semarang City. Technical analysis of the data in this research is descriptive analysis and quantitative descriptive percentage. Results of the research: 1) as much as 67% of residents in housing policy violates BSB KDB. 2) Shape Housing policy violations building coverage in Housing BSB is the beginning of the construction of homes and home renovation. 3) The reason for Housing Policy violations building coverage in BSB is the knowledge of this policy of the Semarang City, home renovation, length of stay and number of occupants. 4) Map landing priority handling building coverage violation split over 3 levels.